Hydroureteronephrosis in women with pelvic organ prolapse: a prospective cohort study - Kumari, Pushplata; Ebenezer, Emily Divya; Salomi, Caroline; Londhe, Vaibhav; Kekre, Aruna Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pelvic organ prolapses (POP) is a common problem in women. The prevalence of POP increase with age. The true prevalence and risk factor for developing hydroureteronephrosis (HUN) in women with pelvic organ prolapse is still unclear due to lack of prospective studies on sufficiently large cohorts. This prospective study was done to study the prevalence of HUN in women with POP and to identify the risk factors for developing HUN. Methods: In this prospective observational study 219 patients were recruited for surgical repair for pelvic organ prolapse for 2 years. Preoperatively, all patients had transabdominal scan to assess the uterus, adnexa and to look for Hydroureteronephrosis (HUN). Women with presence of HUN were followed postoperatively look for the resolution of HUN. Results: The prevalence of bilateral HUN was 6.85%. The mean age of women with HUN ranged from 51-69 years. Diabetes and hypertension were significant risk factor for development of HUN (OR 4.70, 95% CI -1.59-13.88 and OR 3.72, 95% CI- 1.23-11.1 respectively). There was a statistically significant correlation between chronic kidney disease and HUN. (OR 1 with 95%: CI 9.49-30.42). The correlation between stage of pelvic organ prolapse and HUN was not statistically significant (p = 0.062). There was a statistically significant correlation between the duration (2years -15 years) of POP to HUN. (OR 0.233, 95%0.13-0.419). Patients were followed up post operatively for resolution of HUN. HUN resolved in 9 women (60%) and persisted in 6 (40%). Conclusions: The prevalence of bilateral HUN in women with pelvic organ prolapse was 6.8%. Presence of hypertension, diabetes and chronic kidney disease was a risk factor for HUN. HUN resolved in 60% of women after pelvic reconstructive surgery.